Stabilization of activated mast cells by ORAI1 inhibitor suppresses peanut-induced anaphylaxis and acute diarrhea - Gyeongseo Suk; Do Hoon Kwon; Axel Roers; Soman N. Abraham; Hae Woong Choi (Elsevier, 2023)
Mast cell (MC) activation triggered by immunoglobulin E (IgE)-antigen crosslinking involves intracellular Ca2+ influx through the ORAI1 channel, which precedes granule exteriorization and de novo synthesis of mediators. Pharmacologically suppressing MCs via the inhibition of the ORAI1 Ca2+ channel may represent a potential strategy for preventing anaphylaxis. This study demonstrated that peanut-induced anaphylaxis in sensitized mice resulted in significant hypothermia and acute diarrhea. Utilizing the Mcpt5cre-DTA mouse model, we demonstrated that this anaphylactic response was mediated by IgE-antigen-induced MC activation. Prophylactic administration of MC suppressors was an effective means of preventing peanut-induced anaphylaxis. In addition, we observed the potent efficacy of an ORAI1 inhibitor in suppressing the FcεRI-mediated response of murine or human MCs, even when administered concurrently or post-allergen exposure. Mechanistically, the ORAI1 inhibitor was found to prevent the association of Synaptotagmin-2 with the SNARE complex. In an in vivo mouse model of peanut-induced anaphylaxis, the administration of the ORAI1 inhibitor after allergen challenge effectively suppressed allergic acute diarrhea and ameliorated anaphylaxis. Therefore, pharmacological intervention of ORAI1 channel inhibition in MCs represents a promising therapeutic avenue for the treatment of peanut-induced anaphylaxis and acute diarrhea in vivo.